Persepsi Wisatawan terhadap Layanan di Objek Wisata Taman Hutan Raya (Tahura) Ir. H. Djuanda Bandung - Lina Syawalina; Yudi Satriadi; Farhan Basarah (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2022)
The research aims to determine tourist perceptions about the service quality at tourist attraction Tahura Djuanda Bandung. The research method used is descriptive qualitative. The sources of this study are respondents who are a tourist that have visited THR Ir. Djuanda Bandung. The respondents' will fill out a self-administrated questionnaire as they finished walking around at THR Ir. Djuanda Bandung. The number of respondents is 103 people that were determined by the accidental sampling technique. The descriptive analysis uses a mean measuring instrument to determine the average of respondent answers for each question of all variables, every dimension, and the indicator of a variable. To classify the mean of respondents' answers, the class interval method is chosen. In this study, according to the perceptions of tourists who were respondents, based on a value of dimensions of reliability, responsiveness, assurance, empathy, and tangible, the level of service quality at Tahura Djuanda, as one of the tourist attractions in Bandung, proofed as a good category. One line above the medium classification and one line below the excellent classification. The dimension of reliability/trust is the highest dimension that has perceived value of tourist satisfaction by 3.71 on a scale of 1 to 5 and included as a good category. However, the empathy dimension is the lowest dimension of tourist perception value, with a value of 2.96, and becomes the average category. Based on gender, the male tourists' perception of the service quality in Tahura Djuanda is lower than the female tourists' perception. Based on the tourist origin, the foreign tourists' perception about the quality of Tahura Djuandas' service is higher than the tourist from Bandung.